2015
DOI: 10.1007/s11255-015-1146-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between benign prostatic hyperplasia (BPH) and prostate cancer in large prostates: a retrospective data review

Abstract: These results suggest that BPH in large prostates may be protective of PCa. The interaction of the different prostate zones, in particular the transition zone and peripheral zone, may play a significant role in the phenomenon observed in this study. However, sampling error may introduce bias that 12-16 core biopsies in larger prostates may be more likely missing the cancer lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
4
22
0
3
Order By: Relevance
“…A recent study described an inverse relationship between prostate symptom score and PCa 10. Since a prostate symptom score would correlate with prostate volume, this pattern would be expected when compared with the studies mentioned earlier 2,69. However, this study could not show an increase in the accuracy of cancer detection in the multivariate analysis 10.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations
“…A recent study described an inverse relationship between prostate symptom score and PCa 10. Since a prostate symptom score would correlate with prostate volume, this pattern would be expected when compared with the studies mentioned earlier 2,69. However, this study could not show an increase in the accuracy of cancer detection in the multivariate analysis 10.…”
Section: Discussionsupporting
confidence: 39%
“…Several studies have demonstrated a relationship between prostate volume and the incidence of PCa 2,69. These studies have shown an inverse relationship between prostate volume and the incidence of PCa; as prostate volume increases, incidence of PCa decreases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An article published in your journal, by Boehm et al concluded that BPH was associated with an increased risk of PCa, however, this increased risk was limited to BPH diagnosed within the previous year and was more evident with respect to low-grade cancers (Gleason score ≤6) [1]. However, our institution has recently presented data showing an inverse correlation between prostate volume, caused by BPH, and the incidence and aggressiveness of PCa [2,3]. Table 1 below displays the breakdown between incidence and aggressiveness of PCa with respect to prostate volume.…”
Section: Dear Editormentioning
confidence: 75%